Research Study of the Resource School Implementation Project - Machura, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
The article describes an original project to implement a resource school solution, which in the case described is focused on intellectual capital. In addition to the project and the organization, what is important here is the human being – the creator of knowledge and value. The research study is concerned with the academic teaching profession and IT subjects, and as a result, the implementation of the university’s pragmatic mission understood as meeting the needs of society. For this purpose, the author uses Educational Action Research (EAR). The publication presents empirical research based on more than 8 years of experience of a research and teaching employee, documented through sites.google.com. Conclusions are drawn from the 12 edited scientific publications, 17 teaching presentations, and 2 projects popularizing software engineering practices posted in these resources. The author tries to respect the concept of network strategy – understood by the process of value creation using the resources and competencies of all its members. In doing so, the author draws on the practices of relational and network approaches, and seeks to adapt such IT solutions that allow the management of social capital. The possible and expected consequences of the publication, following the keynote of intervention research in education, is a discussion in the teacher‑research community.